Frequency of Severely Elevated Blood Pressure on Admission in Known Hypertensive Patients Presenting with Acute Haemorrhagic Stroke - Irfan, Adan; Simran, FNU; Kumar, Sumeet; Sultan, Umar; Tariq, Salman; Riaz, Sajeela (Archives of Clinical and Biomedical Research, 2023)
Introduction: Acute hypertensive response is the elevation of blood pressure (BP) above normal and premorbid values that initially occurs within the first 24 hours of symptom onset in patients with stroke. Objectives: The main objective of the study is to find the frequency of severely elevated blood pressure on admission in known hypertensive patients presenting with acute haemorrhagic stroke. Material and Methods: This cross sectional study was conducted in Shalamar Hospital Lahore during July 2021 till December 2021. The data was collected with the permission of ethical committee of hospital. Results: In our study total 100 patients were enrolled mean age was 47.7 ± 10 years with minimum age of 18 years and maximum age of 65 years. Lesser patients belong to younger age group (18 years to 40 years) i.e. 54 while 170 belonged to elder age group i.e. 41 year to 65 years 24.1 % and 75.9% respectively. Out of which 62 (27.7 %) were male and 162(72.3%) were female. Conclusion: It is concluded that hypertension were the commonest non communicable diseases (cardiovascular) risk factors in known hypertensive patients imparting with acute hemorrhagic stroke, followed by hypercholesterolemia, smoking, and use of smokeless/chewable tobacco.